2019
DOI: 10.3390/w11081624
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of Satellite-Based Data for Hydrological Mapping of Precipitation and Direct Runoff Coefficient for the Lake Urmia Basin in Iran

Abstract: Water management in arid basins often lacks sufficient hydro-climatological data because, e.g., rain gauges are typically absent at high elevations and inflow to ungauged areas around large closed lakes is difficult to estimate. We sought to improve precipitation and runoff estimation in an arid basin (Lake Urmia, Iran) using methods involving assimilation of satellite-based data. We estimated precipitation using interpolation of rain gauge data by kriging, downscaling the Tropical Rainfall Measuring Mission (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Moreover, gauge observations suffer from sampling errors and undercatch issues (Ehsani & Behrangi, 2021; Kidd et al., 2017; Panahi & Behrangi, 2019; Saemian et al., 2022; Song et al., 2021). Precipitation estimation through gauge data interpolation for sparsely gauged regions is also challenging (Akbari et al., 2019; Yong et al., 2016). Ground‐based precipitation radars provide near real‐time coverage with a high spatiotemporal resolution (Sokol et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, gauge observations suffer from sampling errors and undercatch issues (Ehsani & Behrangi, 2021; Kidd et al., 2017; Panahi & Behrangi, 2019; Saemian et al., 2022; Song et al., 2021). Precipitation estimation through gauge data interpolation for sparsely gauged regions is also challenging (Akbari et al., 2019; Yong et al., 2016). Ground‐based precipitation radars provide near real‐time coverage with a high spatiotemporal resolution (Sokol et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The dry-up of water bodies, i.e. so-called Aral Sea desiccation syndrome (AghaKouchak et al, 2015), has been observed in Central Asia (Micklin, 1988) and northwestern Iran (Akbari et al, 2019;Alborzi et al, 2018;Torabi Haghighi et al, 2018) Hamun Lakes are located in the Iran-Afghanistan border zone in the Sistan region (Figure 1-a) within the transboundary Helmand Basin. The lake system is a Ramsar site (The Convention on Wetlands, 1975) that is crucial for the economy and environment (Rashki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, gauge observations suffer from sampling errors and undercatch issues Kidd et al, 2017;Panahi and Behrangi, 2019;Song et al, 2021). Precipitation estimation through gauge data interpolation for sparsely gauged regions is also challenging (Akbari et al, 2019;Yong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%